Educational platform Edmodo to develop reading Comprehension competence in students of sixth year at escuela de educación básica El Vigía, José Luis Tamayo, salinas, 2014-2015. - Figueroa De La Rosa, William Valentín (2015)
The base of this research is to route the education through technology. Reading is so important in the learning process, and comprehension plays an important role in acquisition of language. Nowadays, the education demands new strategies to teach. One of this is using Information and Communications Technology (ICT) into curriculum. The application of an educational platform is another strategy for using technology in class or autonomous work. The idea of this research is to take small steps in the learning process, to mix reading comprehension strategies and the Educational Platform Edmodo, important factor in the acquisition of language. This research is focused on the importance of reading comprehension and the use of technology, and using the Educational Platform Edmodo so teachers have other options to train the new era of students. Applying several methods as qualitative, quantitative, and so on, this research will try to optimize teaching strategies of reading comprehension, and the development and construction of knowledge using the Educational Platform Edmodo in students of sixth year at school de education basic El Vigia in school year 2014-2015.